Molecular Simulation-Based Drug Repurposing of Thioridazine and Losartan for Targeting CXCR4 and CCR5 Chemokine Receptors in Breast Cancer - Priskila, Dhea; Tomodok, Angelo Christiano Aouad; Basuki, Beatrice Valerie; Pratama, Carissa Putri; Nathaniel, Carolyn; Muhsin, Aishah; Yang, Cheryl; Bappedyanto, Daisy Jemima; Parikesit, Arli Aditya (Journal of Science and Technology, 2026)
Breast cancer remains the most prevalent and fatal cancer worldwide, with chemokine receptors CXCR4 and CCR5 driving tumour growth, metastasis, and immune evasion. This study tested Thioridazine (a phenothiazine antipsychotic) and Losartan (an angiotensin II receptor blocker) as repurposed inhibitors targeting both receptors. Molecular docking via CB-Dock2 showed identical CXCR4 binding for both compounds (?8.2 kcal/mol), while Losartan (?7.1 kcal/mol) outperformed Thioridazine (?6.5 kcal/mol) at CCR5. Anisotropic Network Model (ANM) analysis in ProDy 2.6.1 gave per-residue RMSF of 0.808 Å (CXCR4) and 0.615 Å (CCR5); CCR5–Losartan showed the highest H-bond persistence (100.0%; ?8.286 kcal/mol via AutoDock Vina). SwissTargetPrediction confirmed mechanistic convergence: Thioridazine's targets (DRD2–DRD4) share the G?i/o–cAMP–PI3K–STAT3 cascade with CXCR4, while Losartan's AGTR1 blockade suppresses NF-?B-driven CCL5 secretion, attenuating CCR5 activation. Losartan demonstrated stronger CCR5 binding, greater structural stability, and dual-pathway convergence, warranting priority for in vitro and in vivo validation.